Current-Induced Helicity Reversal of a Single Skyrmionic Bubble Chain in a Nanostructured Frustrated Magnet - Hou, Zhipeng (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.